2011
DOI: 10.1111/j.1748-1716.2011.02367.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for protein‐mediated fatty acid efflux by adipocytes

Abstract: Aim The hormonally controlled mobilization and release of fatty acids from adipocytes into the circulation is an important physiological process required for energy homeostasis. While uptake of fatty acids by adipocytes has been suggested to be predominantly protein-mediated, it is unclear whether the efflux of fatty acids also requires membrane proteins. Methods We used fluorescent fatty acid efflux assays and colorimetric assays for free fatty acids and glycerol to identify inhibitors with effects on fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Importantly, the efflux of glycerol upon lipolytic stimulation by forskolin or isoproterenol was not suppressed by knockdown of Slc43a3, thus the actions of Slc43a3 were specific for FA efflux and were observed whether C12 or C16 fatty acids were examined. This dissociation between FA and glycerol efflux is similar to prior observations where a chemical inhibitor was identified that blocked FA, but not glycerol, efflux (10) However, experiments utilizing triacsin to inhibit ACSL activity, and thus (re)esterification, had no effects on the blockade of lipolytic-stimulated FA efflux in the setting of Slc43a3 knockdown, suggesting that (re)esterification does not contribute to the effects of Slc43a3 on FA efflux.…”
Section: Effects Of Slc43a3 On Camp and Atp Levelssupporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, the efflux of glycerol upon lipolytic stimulation by forskolin or isoproterenol was not suppressed by knockdown of Slc43a3, thus the actions of Slc43a3 were specific for FA efflux and were observed whether C12 or C16 fatty acids were examined. This dissociation between FA and glycerol efflux is similar to prior observations where a chemical inhibitor was identified that blocked FA, but not glycerol, efflux (10) However, experiments utilizing triacsin to inhibit ACSL activity, and thus (re)esterification, had no effects on the blockade of lipolytic-stimulated FA efflux in the setting of Slc43a3 knockdown, suggesting that (re)esterification does not contribute to the effects of Slc43a3 on FA efflux.…”
Section: Effects Of Slc43a3 On Camp and Atp Levelssupporting
confidence: 85%
“…Specifically, there is a debate on the rate-limiting step in the overall process of FA uptake and if, and to what extent, one or more membrane-associated proteins could facilitate and/or regulate FA uptake. In contradistinction, fatty acid efflux from adipocytes is attributed to diffusion without any proteins being associated with facilitating the process, though we previously reported evidence to suggest the possibility of a protein facilitated process (10).…”
Section: Introductionmentioning
confidence: 77%
“…MRP1/ABCC1 is a high-affinity transporter of reduced glutathione (GSH)-conjugated eicosanoids and is also active in transport of drugs and toxic agents, which can lead to GSH depletion and oxidative stress (Henkin et al, 2012). MRP2/ABCC2 functions in the transport of bilirubin, LTC 4 , and glucuronide-conjugated acetaminophen, and defects in this transporter are responsible for hyperbilirubinemia in Dubin-Johnson patients.…”
Section: Metabolism Of Eicosanoids In Metsmentioning
confidence: 99%
“…However, their importance in metabolic disease is evident from reduced expres­sion of the efflux transporter in models of NAFLD (Lickteig et al, 2007) and the recent report of a FA efflux transporter in adipocytes (Henkin et al, 2012). Central to understanding the role of eicosanoid transporters in metabolic disease is the characterization of transporter involved in transcellular eicosanoid metabolism and regulatory roles of eicosanoids for the activity of the FA transporter in liver, pancreas, adipose and muscle tissue (Folco & Murphy, 2006).…”
Section: Metabolism Of Eicosanoids In Metsmentioning
confidence: 99%
“…) and the DIDS‐sensitive proteins of the adipocyte cell membrane (Henkin et al . ) are among the physiological factors currently under investigation for their anti‐obesity drug target potential. Pharmaceutical PPARγ activation is another candidate, positively affecting accumulation as well as saturation status of intramuscular lipids (Harasim et al .…”
mentioning
confidence: 99%